Pelatihan Teknik Analisis dan Sintesis Jurnal Ilmiah untuk Menunjang Keterampilan Menulis Karya Ilmiah Guru Sekolah Dasar dengan Mitra SDN 7 Mataram - Subarinah, Sri; AA, Sukarso; Darmiany, Darmiany (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
A professional teacher must demonstrate four good competencies in terms of personality, pedagogic, professional and social competencies. Some of these four competencies are also directly related to a teacher's career, which is a requirement for a teacher's promotion. This requirement is an obstacle because not all teachers do it for various reasons, including teachers lacking in producing scientific work such as published scientific articles. Teacher publications are very limited in existence. This Community Service activity aims to provide and apply knowledge related to techniques, compiling narratives and scientific arguments for the purposes of writing a scientific article. To achieve these objectives, the workshop method of journal article management is used, which is carried out by brainstorming to find and determine journal themes, exploring and downloading scientific journal articles, reviewing and analyzing journals, summarizing the results of the analysis and mapping them in the analysis results table, paraphrasing, synthesizing journals using the Mendeley application. The synthesis product will be developed independently by the participants but still monitored by the team to ensure the participants' work is smooth and successful. These abilities and skills become the basic capital of participants in compiling arguments, explanations or synthesis of articles, research proposals and other scientific works. Thus, the result of this service is that participants understand the concept of professional work development and the importance of improving the quality and quantity of professional work development work in the form of articles, research proposals, reporting research results and other scientific works